The Trend of Hijrah: New Construction of Urban Millennial Muslim Identity in Indonesia - Farchan, Yusa'; Rosharlianti, Zulfa (The Sociology of Islam, 2021)
The emergence of the hijrah movement in Indonesia, both in public and virtual public spaces, marks the revival of the spirit of Islam in the country. This study examines the following issues: how do urban millennial Muslim communities interpret hijrah?; what is the new construction of urban millennial Muslim identity in Indonesia?; and what is the tendency of the preferences of urban millennial Muslims towards the literacy of Islamic da'wah content? This study uses qualitative methods. The survey population was millennial Indonesian urban Muslims, while the study sample consisted of 110 urban millennial Muslims in the Greater Jakarta area. The results of the study indicate several things. First, the millennial generation of urban Muslims interpret hijrah as "changing attitudes, behavior and lifestyles in a direction that is better in accordance with Islamic values". Second, hijrah has represented an urban Muslim identity constructed as "Devout Muslims", which is characterized by the piety of individuals in public spaces, adherence to the practice of worship, and the use of religious symbols or identities inherent in the activities of urban Muslim community life. Third, in the perspective of economic sociology, hijrah is not only a religious phenomenon but also the behavior and lifestyle of contemporary urban Muslim societies. Fourth, the hijrah community is a liquid community because it is not bound by the same background (ideology or religious social organization). Fifth, the most common source of da'wah literacy followed by hijrah Muslims is YouTube (46%). The most preferred ustadz is Hanan Attaqi (45.45%).